An exploratory study of the work unit housing system in the urban housing reform in Nanning City, China : problems and prospects - Li, Hongyuan; Yap, Kioe Sheng; Amin, A.T.M. Nurul; Foo Tuan Seik; Maih, M. A. Quader; The Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1992)
Work unit housing is a distinct characteristic of China's urban housing system . Most urban h ousing is developed and managed by various work units. A n e w urban hou s i ng policy, initi ated by the gov e rnment of the Peop l e's Republic of Ch i na with the aim to resort to market transactions, will fundamentally c hallenge the important ro l e of work unit housin g. This exp l oratory study contributes a better understanding of the situation and prob l ems of the work unit housin g system a nd its poten tial to deal with t he housing problems a nd issues under the new social and econ om i c c i rcumstances. Basically, this research questionn a ire s urvey a mo ng work stud ies of new work unit housing availab l e secondary data was research. was conducted unit househo ld s and approaches in Nanning also extensively used through a three case City. The in this Cost recovery and misma tch of individual's housing needs and inequity to access h ousing are the main weaknesses in the present wo rk unit housing system. However, the experience of the new wor k un it housing approach - co llecting individual financial resou rces for h ouse bu i lding a nd work unit based housing co operat ive - shows that the work unit housing system has the abi lity to tackle these prob l ems . Instead of elimi n ating t h e unfa irn ess of the existing hou s ing system, the public hou se sales program could worsen the situation. Ho useholds with high i ncome and good housing condit i ons will get more benefits from purchasing the dwelling unit at high ly s ubsidized Prices. Wor k unit based cooperat i ve hou sing is a effective altern at ive to deal with this new issue through c o -owners h ip patterns. Based on the research findings, it is concluded that unit housing must be promoted rather than constrained, and there is much room for improvement.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology
Keywords: Housing -- China -- Nanning